ANALISIS PERBEDAAN KINERJA KEUANGAN ANTARA BANK KONVENSIONAL DENGAN BANK SYARIAH - Eskasari Putri; Arief Budhi Dharma (Universitas Muhammadiyah Surakarta, 2016)
This study aimed to compare the financial performance betweenConventional Bank and Islamic Bank measured by the ratio of CAR, NPL, ROA, ROE, and LDR at Conventional Bank and Islamic Banking is still under the name of one company that went public in the year 2011 to 2013.This research is a quantitative descriptive. The data usedfrom the form of annual financial statements of banks sampled in the study period of 3 years. While the sample is determined by purposive sampling method to obtain 14 banks, consisting of 7 Conventional Bank and 7 Islamic Bank. Types of data used are secondary data obtained from www.bi.go.id. The analytical method used is different test parametric paired sample T-test, based on two different types of tests used in this study stated that the results obtained CAR ratio between Conventional Bankand Islamic Bank there is a difference, but not significant, while the NPL ratio, ROA, ROE, and LDR has a significant difference. Keywords: CAR, NPL, ROA, ROE, LDR